Les résidents secondaires, des acteurs essentiels des systèmes touristiques littoraux français ? - Caroline Blondy; Luc Vacher; Didier Vye (Territoire en Mouvement)
Coastal zones are generally concerned with an important attractiveness. Second homes play a major part in this coastal pressure, first of all because of their number, but they also represent numerous touristic accommodations and contribute to the local economy. Second homes owners are somewhere between inhabitants and tourists, they are an example of new arts of dwelling and they are also a very controversial issue. We assume that, far from being “secondary”, this population takes a full part in their territories dynamics, especially in coastal and tourist zones. Nevertheless, owners’ habits, representations and expectations are not very known, especially in coastal and tourist zones. That’s why our research group has conducted in 2013 a study about second homes owners’ habits in Charente-Maritime main destination of coastal tourism in France. To begin with, we propose to show the interest but also the difficulty to study second home owners within the framework of tourism coastal territories. Secondly, we detail the survey protocol we made in the case of Charente-Maritime. Thirdly, we will analyze some of the results collected in 2013 in order to assess to which extent second home owners really are stakeholders of tourism coastal territories.